THE USE OF ENGLISH IN TAGLINE OF ADVERTISEMENTS FOR PRODUCTS PUBLISHED BY INDONESIAN NEWSPAPER - MARIAM, SITI (VISION, 2014)
ABSTRACT When human life is still simple, they can find their daily needs easily. With the progressiveness of era, their life is complex. They do not have a lot of time to look for what and how goods or services that they need. For solving the problem, it occurs advertising activities, id. est. an activity introduces a product to public through advertising media such as newspaper, magazine, radio, television, film, internet, etc. Apart from information tool, an advertisement also functions as persuasive tool, therefore the copy writers try to make their advertisement as attractive as possible with expectation it can influence the consumersâ attitude and behavior. Advertisement in printed media consists of two elements, namely pictures and verbal symbols that form words, idiom, phrase or sentences. The writer will discuss English in tagline of advertisements, which tends to be persuasive function, from the linguistics point of view. Â  Keywords : tagline, advertisement, newspaper.